Technical and socioeconomic constraints to the domestication and functionality of biogas technology in rural areas of southern Ethiopia. Issue 1 (1st January 2020) - Sime, Getachew
Abstract: Although biogas technology has been introduced as a national program to respond to the ever-increasing energy demand in Ethiopia, empirical studies on the technical, institutional and socioeconomic constraints to the domestication and functionality of the technology are scant. Thus, this study provides an overview of these constraints. The study is based on, key-informant interviews, legislation and strategy documents, extensive literature reviews and observation of bio-digesters. Limitations in technical, economic, sociocultural and institutional perspectives are the major factors constraining the domestication and functionality of the technology. The constraints pertain to the adequacy of institutional follow-up; management of bio-slurry; availability and cost of maintenance service; price, availability and accessibility of appliances at local markets; availability of credit associations; adequacy of masons skill; skill and level of awareness of users; and sociocultural acceptance to connecting toilets to bio-digesters. Primarily, these constraints emanate from the weak organizational and institutional alignment among key stakeholders. Thus, for the realization of sustainable domestication of the technology and renewable energy policy, there is a need to emphasize on dissemination, monitoring and ownership strategies as well as on operationalizing institutional commitments.